The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4081/jlimnol.2016.1183
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bosmina size structure to the acidification and recovery of lakes near Sudbury, Canada

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
(112 reference statements)
0
14
0
1
Order By: Relevance
“…Paleolimnological studies suggest that cladoceran and diatom communities in some recovering lakes are not moving back to their historical conditions, but rather they are moving to new states, likely because of climate warming (Labaj et al 2016;Sivaraja et al 2016Sivaraja et al , 2017. increasing the invasibility of northern lakes (Edwards et al 2016;Van Zuiden et al 2016).…”
Section: Shifting Reference Conditionsmentioning
confidence: 99%
“…Paleolimnological studies suggest that cladoceran and diatom communities in some recovering lakes are not moving back to their historical conditions, but rather they are moving to new states, likely because of climate warming (Labaj et al 2016;Sivaraja et al 2016Sivaraja et al , 2017. increasing the invasibility of northern lakes (Edwards et al 2016;Van Zuiden et al 2016).…”
Section: Shifting Reference Conditionsmentioning
confidence: 99%
“…longirostris have shown that increased temperature, acidification, and metal contamination are key factors in enhancing the occurrence of morphotypes with short antennules (Labaj et al, 2016;Sakamoto & Hanazato, 2009 reproductive traits under conditions of toxicant stress (Baird, Barber, & Calow, 1990;Knops, Altenburger, & Segner, 2001). A decline in reproduction may be considered to be directly caused by a harmful factor but the results of our study suggest that low levels of reproduction and long lifespan may be a direct defensive choice in B.…”
Section: Discussionmentioning
confidence: 63%
“…This experiment also showed that morphotypes with low reproductive efficiency are naturally favoured in populations exposed to suboptimal abiotic conditions. A few reports on the influence of abiotic conditions on the phenotypic structure of B. longirostris have shown that increased temperature, acidification, and metal contamination are key factors in enhancing the occurrence of morphotypes with short antennules (Labaj et al, ; Sakamoto & Hanazato, ). In general, these observations are in agreement with our results, for typica , dominant in the NaCl‐population, has quite short appendages.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, various empirical studies suggest that B. longirostris is not preferred by fishes because it has a relatively small body size [60]. Bosmina longirostris is more vulnerable to invertebrate predation, such as by copepods, than to predation by fish [61,62]. Thus, B. longirostris can often dominate rivers and streams supported by a high abundance of fishes [61].…”
Section: Behavioral Strategies By Body Size Class Of the Two Cladocermentioning
confidence: 99%